Correlation Between Nasal Epithelial Injury and In Vitro Cytotoxicity Using a Series of Small Molecule Protein Tyrosine Phosphatase 1B Inhibitors Investigated for Reversal of Leptin Resistance in Obesity. (July 2017) - Brown, Alan P.; Saravanan, Chandrassegar; Devine, Patrick; Magnifico, Maria; Gao, Jiaping; Beaulieu, Valerie; Ma, Fupeng; Yasoshima, Kayo; Barnes-Seeman, David; Yamada, Ken
This research provides a cautionary example when evaluating changes in behavioral end points with respect to postulated pharmacologic activity. Various small molecule substrate mimetic protein tyrosine phosphatase 1B (PTP1B) inhibitors were investigated as pharmacologic agents for decreasing food consumption using intranasal (IN) dosing as a means for direct nose-to-brain delivery along the olfactory/trigeminal nerve pathways. Although food consumption was decreased in diet-induced obese (DIO) mice, nasal discharge was observed. Studies were conducted to investigate local effects on the nasal airway and to develop structure–activity relationships. Intranasal administration of PTP1B inhibitors at ≥0.03 mg/d to DIO mice produced dose-dependent injury to various cell types of the nasal epithelia. Protein tyrosine phosphatase 1B inhibitors with calculated log octanol >3.0 were the most toxic. Whereas a pharmacologically inactive analog of a PTP1B inhibitor produced nasal injury, along with decreased food consumption, the marketed IN drug ketorolac produced no lesions at the same dose of 0.3 mg/d and only minor changes at 3 mg/d. Rat skin fibroblast cells were exposed in vitro to PTP1B inhibitors, ketorolac, paraquat, and the detergent sodium dodecylbenzene sulfonate (NDS) followed by measures of cytotoxicity. The most potent PTP1B inhibitors were similar to NDS, whereas ketorolac was the least toxic compound. Cytotoxic potency in vitro was similar to in vivo. In conclusion, PTP1B inhibitors injured nasal epithelium through a mechanism independent of PTP1B inhibition and likely due to nonspecific cytotoxicity such as disruption of the cell membrane. Decreased food consumption in DIO mice was due to toxicity rather than a pharmacologic mode of action.